Exploitation of Soybean Oil Acid Degumming Waste: Biocatalytic Synthesis of High Value Phospholipids. Issue 34 (12th September 2021) - Allegretti, Chiara; Bono, Andrea; D'Arrigo, Paola; Gatti, Francesco G.; Marzorati, Stefano; Rossato, Letizia A. M.; Serra, Stefano; Strini, Alberto; Tessaro, Davide
Abstract: The acid degumming waste of the seeds oil refining industry is currently disposed of, but, instead, it could be exploited as an important source for the preparation of many products. In this work, the waste coming from the soybean oil refining step was first recovered and treated, allowing the isolation of a fraction enriched of phospholipids (PLs). Then, the latter was transformed, via an enzymatic reaction catalysed by phospholipase D (from S treptomyces netropsis ), into more valuable products: polar head modified PLs‐enriched mixtures containing phosphatidylserine (PS), phosphatidylglycerol (PG), phosphatidylethanolamine (PE) and phosphatidylhydroxybutyrate (PB). In the following we show how biocatalysis can be exploited for the production of value‐added PLs, to be used as functional food and nutraceutical ingredients, from a renewable feedstock. This alternative to the industrial usual disposal procedures should impart to the whole process a greater value in terms of carbon recycling, in agreement with the paradigms of bioeconomy for a wiser reuse of renewable resources in a circular economy perspective. Abstract : This work focused on the treatment and the biocatalytic transformation of the waste residue coming from the acid water degumming, one of the first steps in edible soybean oil refining. This complex by‐product, which is rich in phospholipids, is usually disposed of but has been here transformed in high value polar head modified phospholipids providing an alternative approach to the simple disposal in a perspective of circular economy.